Amino acid uptake by dorsal root ganglia from streptozotocin-diabetic rats. - Thomas, P K (1984)
Dorsal root ganglia from streptozotocin-diabetic rats and age- and weight-matched control animals were incubated with 4-amino 3H-butyric acid. A significant reduction in uptake was observed in the diabetic animals. The incorporation of 3H-leucine into protein was also significantly reduced but the results did not allow a conclusion as to whether this was a secondary or an independent effect. These findings are discussed in relation both to the abnormalities known to develop in diabetic rats and to the causation of human diabetic neuropathy.